Long-term predictivity of early neurological assessment and developmental trajectories in low-risk preterm infants - Dicanio, Daniela; Spoto, Giulia; Alibrandi, Angela; Minutoli, Roberta; Nicotera, Antonio Gennaro; Di Rosa, Gabriella (Frontiers in Neurology, 2022)
Prematurity represents 10.6% of all births, and although preterm infants usually show adequate neurodevelopmental outcomes, some may develop significant and long-lasting neurological sequelae. Many studies have analyzed predictive factors for developing severe neurodevelopmental impairments (cerebral palsy, other motor and socio-relational disorders such as autism, etc.). In this study, 148 preterm infants were enrolled to investigate the neurodevelopmental trajectories in a population of low-risk premature infants using standardized assessment methods. Significant correlations were found between the general movements, the Hammersmith Infant Neurological Examination and the Griffiths Mental and Development Scales. Moreover, this study showed their validity and predictivity for adverse neurodevelopmental outcomes even in low-risk infants.